Microbubble treatment of cinnamon leaves for enhancing the quality of mulled rice wine - Ping-Hao Huang; Samuel Herianto; Kuan-Chen Cheng; Chang-Wei Hsieh; Hsiu-Ling Chen; Min-Hung Chen; Chih-Yao Hou; Ming-Kuei Shih (International Journal of Food Properties, 2025)
The use of herbs such as cinnamon leaves is a well-established practice to enhance the sensory attributes and physicochemical properties of wine and related beverages. Traditionally, spices are added directly during fermentation, a method that may limit the efficient release of key aromatic compounds. We present a microbubble (MB) treatment of cinnamon leaves prior to wine fermentation. Optimized MB conditions significantly increased the levels of major aromatic compounds (cinnamaldehyde, cinnamyl acetate, and coumarin), in cinnamon leaf powder. When applied a 10-day wine fermentation, the MB-treated cinnamon leaves (treatment O, 4.5 kg/cm2, 50°C, and 5 min) markedly improved key physicochemical characteristics of the wine, including pH (4.18 ± 0.01), titratable acidity (900 g/L), total soluble solids (16.93 ± 0.05°Brix), alcohol content (16%), residual sugar (118.3 ± 0.86 g/L), and total phenolic content (201.35 ± 0.007 mg GAE/L). Additionally, treatment O produced liquor with significantly enhanced flavor, smoothness, and aftertaste compared to both the control and other MB treatments (p < 0.05). Wines derived from MB-treated cinnamon O also exhibited notable antioxidant activity. Collectively, our findings demonstrate the potential of MB-treated cinnamon leaves as a novel and effective mulling agent to elevate the sensory and chemical quality of wine.